Propuesta metodológica para el diseño de aulas virtuales en Moodle - Cedeño Tapia, Víctor Javier (Machala: Universidad Tëcnica de Machala, 2022)
In the present work the methodology for the design of virtual classrooms in Moodle is analyzed. The Moodle platform is a means used to manage virtual communication that allows teaching-learning to be developed in a more dynamic, reflective, attractive way, with a flexible schedule. The general objective of the research is: To make a methodological proposal for the design of virtual classrooms in Moodle that contribute to improving the process of teaching mathematics in Higher Education Institutions. ICTs have been incorporated into education in the same way that they have done so in the rest of the productive, communication, social, research and development activities, etc. This incorporation has been framed in a situation of social changes as well as in education Regarding the methodology, this is qualitative, descriptive and applied, the population corresponds to 248 students, between men and women from the Technical University of Machala, from the Faculty of Civil Engineering and the sample amounts to 69 students. With the results obtained from the research, the methodological proposal is made. The students, during the investigation, have expressed their comfort with the use of virtual tools, for the most part they are receptive to the teachings given by the teachers through these means. It is evident that currently a large part of the universities are committed to the development of competencies that are related to skills, knowledge and attitudes, implementing educational methods that make possible the efficient use of technological tools, especially Moodle.
En el presente trabajo se analiza la metodología para el diseño de aulas virtuales en Moodle. Esta plataforma es una herramienta utilizada para gestionar la comunicación virtual y permite hacer que la enseñanza sea más dinámica así como atractiva y reflexiva, con horario flexible. El objetivo general de la investigación es: Realizar una propuesta metodológica para el diseño de aulas virtuales en Moodle que contribuyan a mejorar el proceso de enseñanza de las matemáticas de las Instituciones de Educación Superior. Las Tics se han incorporado a la educación de la misma manera que lo han hecho en el resto de las actividades productivas, de comunicación, sociales, de investigación y desarrollo, etc. Esta incorporación se ha enmarcado en una situación de cambios tanto sociales como en la educación. En cuanto a la metodología de investigación, esta es de tipo cualitativa, descriptiva y aplicada, la población corresponde a 248 estudiantes, entre hombres y mujeres de la Universidad Técnica de Machala, de la Facultad de Ingeniería Civil y la muestra asciende a 69 estudiantes. Con los resultados obtenidos de la investigación se realiza la propuesta metodológica. Los estudiantes, durante la investigación han manifestado su comodidad con el uso de herramientas virtuales, en su mayoría se muestran receptivos a las enseñanzas impartidas por los docentes a través de estos medios. Es evidente que actualmente gran parte de las universidades se encuentran comprometidas con el desarrollo de competencias que se relacionan con las habilidades, conocimientos y actitudes, implementando métodos educativos que hacen posible el uso eficiente de herramientas tecnológicas en especial de Moodle.
Keywords: HERRAMIENTA VIRTUAL; MOODLE; AULA VIRTUAL; ENTORNO VIRTUAL